PENGARUH EMOTIONAL QUOTIENT (EQ) TERHADAP GAYA KEPEMIMPINAN, STRES KERJA, DAN KEPUASAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN DI PT. KARYA TEKNIK MAKMUR - Madali, Claudia; Purnama, Eka Desy (Manajemen Bisnis Kompetensi, 2014)
ABSTRACTÃ‚Â The purpose of this study was to determine the influence of Leadership Style, Job Stress, and Emotional Quotient Corporate Loyalty to the performance of the employees of PT. Karya Teknik Makmur and which variables that have the most impact on the performance of employees of PT . Karya Teknik Makmur.Ã‚Â Keywords: Ã‚Â Emotional Quotient, Leadership Style, Job Satisfaction, Job Stress, Employee PerformanceÃ‚Â